HUBUNGAN REGULASI EMOSI DAN DUKUNGAN SOSIAL DENGAN SUBJECTIVE WELL-BEING PADA MAHASISWA YANG MENGALAMI QUARTER LIFE CRISIS - Oktavia, Mirta Dwi; Fahmawati, Zaki Nur (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to explore the relationship between emotion regulation and social support with subjective well-being in college students who experience quarter-life crisis. This research is a quantitative study with a multiple correlational approach. The population in this study were 23,039 students in Sidoarjo based on the Central Bureau of Statistics in 2022. The sampling technique used in this study was purposive sampling technique. This study shows that an insignificant negative relationship was also found between social support and subjective well-being (r=-0.063, p=0.248). This means that the higher the social support received, the subjective well-being tends to decrease, although this relationship is also not strong enough to be meaningful. This finding contradicts previous research which generally shows that social support contributes positively to subjective well-being.